An ingenious multiple communicator concept for next generation smart metering communication system - Hashim W.; Ismail A.F.; Raj Mohamed R.M.A.; Hasan M.K.; Halim M.I.A.; Kumanan K. (Science and Engineering Research Support Society, 2023)
Advanced metering infrastructures; Automation; Intelligent buildings; Numerical methods; Smart meters; Actual measurements; Multiple broadband; Multiple connections; Predictive analytics; Selection mechanism; Similar pattern; Smart homes; Study scenarios; Electric measuring instruments